Care of Stroke Patients: A Study Based on The Islamic Perspective - Husen Ismail, Faisal; Destari, Dina; Kirin, Arwansyah; Borham, Abd Shakor; Mohd Khalid, Halimi; Masrur, Muhammad (2024)
A stroke is one of the diseases caused by the narrowing of blood vessels to the brain or blood vessels bursting. This results in pain and disability in stroke patients. In Malaysia, stroke has become the second highest cause of death. The pain and disability of stroke patients cause them to need the help of others in managing their needs. The aim of our study was to explore the issues faced in the care of stroke patients. In addition, this study also explores the issue of care for stroke patients from an Islamic perspective. This study is qualitative in form where the primary data of the study refers to journal writings, books, and newspapers. When the description is related to the Islamic perspective, it refers to two main references which are alQuran and al-Hadith. The study found that the situation of stroke patients from the point of view of movement limit, communication difficulties, cognitive impairment, emotional changes, and medical management, requires a caregiver who can understand the needs of the patient. This study also found that the Qur'an and al-Hadith emphasize the need to help people suffering from a stroke in the form of order to help people who need help. The findings of this study provide information on issues related to stroke patients. This information can help stroke patient caregivers, especially family members in adjusting patient-centered care and providing better management.